2019
DOI: 10.1080/00014788.2019.1647127
|View full text |Cite
|
Sign up to set email alerts
|

Deprivation, social class and social mobility at Big Four and non-Big Four firms

Abstract: Using the work of Bourdieu and Savage, this paper investigates social class and social mobility among chartered accountants who qualified with The Institute of Chartered Accountants of Scotland in 2009. We find that these accountants tend to come from privileged backgrounds and that those who qualified with Big Four firms possess more economic, social and cultural capital than those who qualify with other firms. Our study provides fresh insights into how elements of social class interact with social background… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 72 publications
(104 reference statements)
0
7
0
Order By: Relevance
“…Among them, the studies that examined a gender gap that favours male employees should be highlighted (Frear et al., 2019; Martin, 2017). Similarly, other studies have shown that age, marital status, and socioeconomic status also affect employment outcomes (Jackson, 2014; Paisey et al., 2020).…”
Section: Determining Factors Of Labour Market Outcomes Among Recently Graduated Studentsmentioning
confidence: 60%
See 1 more Smart Citation
“…Among them, the studies that examined a gender gap that favours male employees should be highlighted (Frear et al., 2019; Martin, 2017). Similarly, other studies have shown that age, marital status, and socioeconomic status also affect employment outcomes (Jackson, 2014; Paisey et al., 2020).…”
Section: Determining Factors Of Labour Market Outcomes Among Recently Graduated Studentsmentioning
confidence: 60%
“…The debate about integrating new students into higher education, however, has lacked deeper reflection on how to support the career development of socially underrepresented graduates. While helping students be successful during post-high school education is a highly relevant matter, it is also important to examine the way in which these new students join the labour market, since it is known that they face greater challenges when developing their careers (Garriott, 2020; Gibbons & Woodside, 2014; Paisey et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies indicate how cultural capital, accrued from prestigious education and qualifications, is key to gaining distinction in accountancy (Ashley and Empson 2017; Spence et al 2017). Spence et al (2015) link professional power and distinction to globalization after exploring how, in four Western countries (United Kingdom, Spain, France, and Canada), the terms for promotion to partner levels in Big 4 firms are closely aligned with economic capital (see also Barrett et al 2005; Harvey et al 2020; Paisey et al 2020).…”
Section: Globalization Power and Distinction In The Accounting Profes...mentioning
confidence: 99%
“…The term 'social mobility' was first introduced in 1920, being used broadly by Sorokin to refer to the movement of individuals within social spaces. It is often used to refer to the movement of individuals within the social hierarchy, often as a result of individuals' efforts to increase their power, status, or prestige (Paisey, Paisey, Tarbert, & Wu, 2020). Mobility has been strongly influenced by industrialization and economic development; at the same time, however, it has been positively correlated with income gaps and immigration (Yaish & Andersen, 2012).…”
Section: Social Mobility: a Factor In Socio-cultural Changementioning
confidence: 99%